2018
DOI: 10.1093/hropen/hoy011
|View full text |Cite|
|
Sign up to set email alerts
|

The rate of euploid miscarriage is increased in the setting of adenomyosis

Abstract: STUDY QUESTION Does the rate of miscarriage increase in the setting of adenomyosis independent of other known risk factors for miscarriage such as maternal age, BMI, embryo genetic status? SUMMARY ANSWER Adenomyosis and high BMI both significantly increase miscarriage risk independent of each other, maternal age and embryo health. This study is the first to suggest that ultra-long down regulation GnRH agonist treatment may reduce the rate of early pregnancy loss in aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 30 publications
3
54
1
Order By: Relevance
“…Adenomyosis has been associated with an increased risk of abortion and a decreased chance of natural conception, and was regarded as one of the major contributors to infertility [3]. A study of 171 women showed that patients with adenomyosis have a significantly higher rate of miscarriage than those without it [18]. A meta-analysis that included 11 comparative studies found that women with adenomyosis have lower rates of implantation, clinical pregnancy, and live birth [19].…”
Section: Discussionmentioning
confidence: 99%
“…Adenomyosis has been associated with an increased risk of abortion and a decreased chance of natural conception, and was regarded as one of the major contributors to infertility [3]. A study of 171 women showed that patients with adenomyosis have a significantly higher rate of miscarriage than those without it [18]. A meta-analysis that included 11 comparative studies found that women with adenomyosis have lower rates of implantation, clinical pregnancy, and live birth [19].…”
Section: Discussionmentioning
confidence: 99%
“…The adenomyotic uterus provides a dysfunctional environment for the maintenance of pregnancy [2,15]. Mechanisms may include uterine dysperistalsis, abnormal concentrations of free radicals in the uterine environment, and altered endometrial vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, because more women are delaying childbearing until their late 30 s or 40 s, adenomyosis is being diagnosed more frequently in infertile patients undergoing in vitro fertilization (IVF). Previous studies have demonstrated that adenomyosis has a signi cant negative effect on the chance of implantation and is associated with a higher miscarriage rate and a lower live birth rate [2][3][4]. Treatment with a gonadotropin-releasing hormone agonist (GnRH-a) has been widely used for adenomyosis.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, 34 women had adenomyosis by TVS and 137 had morphologically normal uterus. Adenomyosis group had signi cantly higher miscarriage rates than the non-adenomyosis group (53% vs.19.7%; P = < 0.0001)29 . Chiang et al performed a case control study in which 19 women with adenomyosis diagnosed by USG and 144 age matched controls with sonographically normal uterus.…”
mentioning
confidence: 84%